Spectrally encoded coherence tomography and reflectometry: Simultaneous en face and cross‐sectional imaging at 2 gigapixels per second. Issue 4 (27th December 2017) - El‐Haddad, Mohamed T.; Bozic, Ivan; Tao, Yuankai K.
Abstract : Non‐invasive biological imaging is crucial for understanding in vivo structure and function. Optical coherence tomography (OCT) and reflectance confocal microscopy are two of the most widely used optical modalities for exogenous contrast‐free, high‐resolution, three‐dimensional imaging in non‐fluorescent scattering tissues. However, sample motion remains a critical barrier to raster‐scanned acquisition and reconstruction of wide‐field anatomically accurate volumetric datasets. We introduce spectrally encoded coherence tomography and reflectometry (SECTR), a high‐speed, multimodality system for simultaneous OCT and spectrally encoded reflectance (SER) imaging. SECTR utilizes a robust system design consisting of shared optical relays, scanning mirrors, swept laser and digitizer to achieve the fastest reported in vivo multimodal imaging rate of 2 gigapixels per second. Our optical design and acquisition scheme enable spatiotemporally co‐registered acquisition of OCT cross‐sections simultaneously with en face SER images for multivolumetric mosaicking. Complementary axial and lateral translation and rotation are extracted from OCT and SER data, respectively, for full volumetric estimation of sample motion with micron spatial and millisecond temporal resolution. Abstract : A novel system design for a multimodal imaging system is presented. The system is designed for combined wide‐field topographic and tomographic imaging at multi‐gigapixel throughput, with potential applications in research and clinical settings. System performance is demonstrated through in vivo human imaging of the anterior chamber and the posterior retina. A preliminary algorithm is outlined that takes advantage of the three‐dimensional motion information to perform multivolumetric mosaicking of ultrawide‐field retinal composites.